Patients' and therapists' experience and perception of exoskeleton-based physiotherapy during subacute stroke rehabilitation: a qualitative analysis. Issue 24 (20th November 2022) - Louie, Dennis R.; Mortenson, W. Ben; Lui, Michelle; Durocher, Melanie; Teasell, Robert; Yao, Jennifer; Eng, Janice J.
Abstract: Purpose: To explore the experience and acceptability of an exoskeleton-based physiotherapy program for non-ambulatory patients during subacute stroke rehabilitation from the perspective of patients and therapists. Materials and methods: This was a qualitative descriptive study using semi-structured interviews and thematic analysis. Fourteen patients with stroke who participated in the experimental arm of a randomized controlled trial investigating the efficacy of exoskeleton-based physiotherapy were recruited. Six physiotherapists who provided the intervention were also recruited. Results: Three themes were identified relating to the experience and acceptability of an exoskeleton-based physiotherapy program: (1) A matter of getting into the swing of things depicted the initial and ongoing learning process of using an exoskeleton; (2) More of a positive experience than anything else described the participants' mostly favorable attitude toward exoskeleton-based gait training; and (3) The best step forward captured participant-identified recommendations and considerations for the future integration of exoskeleton training into stroke rehabilitation. Conclusions: Patients with stroke were even more optimistic than therapists toward the experience and benefits of exoskeleton-based gait training during subacute stroke rehabilitation. Future clinical practice should consider the balance between actual and perceived benefits, as well as the potential barriers to integrating an exoskeleton into stroke rehabilitation. IMPLICATIONS FOR REHABILITATION: Powered robotic exoskeletons can be used to provide higher duration and more repetitious walking practice for non-ambulatory patients with stroke. Patients with stroke view exoskeleton-based physiotherapy highly favorably, attributing greater opportunity and benefit to using the device during subacute rehabilitation. Physiotherapists should consider learning challenges, patient characteristics, and implementation barriers when integrating exoskeleton-based training within a treatment program.